BENTUK-BENTUK STRATEGI PEMERINTAH KOREA SELATAN MEMPERKUAT PENGARUH BUDAYANYA DI ERA GLOBALISASI - Rilo Bagaskoro (HI 16 UMY 133, 2016)
*133 The development of a technology gives benefit to interaction which is offered in this globalization era. Along with the development of technology that occurred, cultural exchanges ensued between one country and another. Along with the shift of security issues to economic issues in international relations, a phenomenon that is not less important is globalization. In this globalization era, anyone can interact with more intensive as there are no geographical boundaries that the state can not be reached. It is caused by rapid technological developments which lead to telecommunications and transportation to be very efficient. In this globalization era, pop culture is something which is being loved by the world nowadays. Pop culture begins with the success of Hollywood to get well known. While recently in South Korea, South Korean pop culture called Hallyu Korean Wave successfully entered and gave its influence in several countries in the world. The aim of this research is to give an explanation according to the success of South Korea in the globalization competition through the forms of South Korean government strategy. Behind the success of South Korean pop culture become something which is well known at a few countries in the world, there is a role of government which is very important in the process of globalizing South Korean pop culture. Politics and culture become a sort of two sides of a coin that can not be separated because these two aspects are always related and can produce a symbiotic mutualism in which the phenomenon of mutual benefit between the two parties in case the interaction process. These results indicate that the role of the South Korean government since the 1990s has managed to turn the country, South Korea to be a better country in the context of pop culture.